Bendamustine Conditioning Skews Murine Host DCs Toward Pre-cDC1s and Reduces GvHD Independently of Batf3 - Molina, Megan S.; Stokes, Jessica; Hoffman, Emely A.; Eremija, Jelena; Zeng, Yi; Simpson, Richard J.; Katsanis, Emmanuel (Frontiers in Immunology, 2020)
Graft-versus-host disease (GvHD) remains the second leading cause of death in allogeneic hematopoietic stem cell transplantation recipients, highlighting the need for improved preventative strategies. Our laboratory has previously demonstrated in an experimental bone marrow transplantation (BMT) model that bendamustine combined with total body irradiation (BEN+TBI) is a safer alternative to cyclophosphamide with TBI (CY+TBI). The biological mechanisms of action of BEN have not been fully elucidated and likely involve multiple cell populations. Host dendritic cells (DCs) can prime naïve donor T-cells immediately following transplantation, making host DCs critical for the initiation phase of GvHD. We hypothesized that BEN+TBI conditioning favorably alters host DC composition to reduce GvHD. We demonstrate that host DCs treated with BEN+TBI induce less allogeneic T-cell proliferation than those conditioned with CY+TBI. We further show that BEN+TBI conditioning results in greater total numbers of all host DC subsets but with a more favorable composition compared to CY+TBI with significantly larger proportions of type 1 conventional DCs (cDC1), a highly regulatory DC subset capable of suppressing GvHD. Our studies using recipient Batf3 KO mice indicate that CD8α+ cDC1s are largely dispensable for the reduced GvHD following BEN+TBI conditioning. We found a higher frequency of host pre-cDC1s with BEN+TBI conditioning in both wild-type (WT) and Batf3 KO mice, which was inversely associated with GvHD. Additionally, we observed that BEN treatment results in greater expression of Flt3 receptor (CD135) on host DCs compared to CY, potentially contributing to the skewing of host DCs toward cDC1s. Further, BEN+TBI conditioning results in host cDCs with greater expression of PIR-B, an inhibitory receptor capable of preventing lethal GvHD. We conclude that BEN+TBI is a safer alternative to CY+TBI, resulting in a greater frequency of host pre-cDC1s and limiting GvHD.